Virtual Sufism Identity in Majelis Kalbun Salim (MKS) - Khotimah, Khusnul; Solikhah, Amirotun; Maulana, Zidan Abid (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2024)
Sufism communities in the digital world have emerged as a form of religious accentuation in the digital era and a space for reflection on religious and social issues. This study aims to disclose the identity of virtual Sufism in Majelis Kalbun Salim (MKS). The research was conducted using qualitative methods with a symbolic interactionism approach. Symbolic interactionism requires the production of meanings created from certain symbols within a community/social group. Data collection techniques included documentation studies and in-depth interviews. Documentation was used to capture and observe the interactions of MKS members in both the virtual and real worlds. Meanwhile, interviews were conducted with Muhammad Yaser Arafat, one of the founders of MKS, Kiai Akrom Solihin, Kiai Abdul Ghodir, and Kang Din Rosyidin as active members. The results of this study explain that the identity of MKS's virtual Sufism is created through two elements: first, the influence of the online study of Ihya' Ulumuddin led by Ulil Abshar Abdalla (Gus Ulil), and second, the production of Sufi humour. MKS members use both as a control medium to continually self-regulate, erode ego and self-importance, discard ideal human attributes, and transcend merely ritualistic practices. Contribution: This study provides another perspective in understanding the form of Sufism in the digital/virtual world. The virtual world is perceived and positioned by Majelis Kalbum Salim members as a medium for deconstructing personal ego in religion so that it transcends ritual aspects alone.